UJI STABILITAS, DAYA APUNG DAN WARNA SERTA AROMA PADA PELET YANG BERBEDA - Yulianto, Tri (Pusat Penelitian Sumberdaya Pesisir dan Laut, Universitas Maritim Raja Ali Haji, Indonesia, 2018)
Riau Archipelago Province is the province that separate from the major city and only can be reach by sea or air. One of the problem in aquaculture business in Riau Archipelago Province is the price of fish feed is expensive because distribute from java and Sumatra island. The solution is by producing the fish feed independently with appropriate composition and accessible material. The low price material and simple test is important to be conducted to see the quality of the fish feed, such as aroma, color, buoyance , sink velocity, and the resilience of the fish feed in the water. All the test can be done by the people independently, so the process can give benefit in producing fish feed for fish and shrimp aquaculture in Riau Archipelago Province.